An antiarch placoderm shows that pelvic girdles arose at the root of jawed vertebrates - Zhu, Min (The Royal Society, 2012)
Almost all gnathostomes or jawed vertebrates (including osteichthyans, chondrichthyans, ‘acanthodians’ and most placoderms) possess paired pectoral and pelvic fins. To date, it has generally been believed that antiarch placoderms (extinct armoured jawed fishes from the Silurian–Devonian periods) lacked pelvic fins. The putative absence of pelvic fins is a key character bearing on the monophyly or paraphyly of placoderms. It also has far-reaching implications for studying the sequence of origin of pelvic girdles versus that of movable jaws in the course of vertebrate evolution. Parayunnanolepis xitunensis represents the only example of a primitive antiarch with extensive post-thoracic preservation, and its original description has been cited as confirming the primitive lack of pelvic fins in early antiarchs. Here, we present a revised description of Parayunnanolepis and offer the first unambiguous evidence for the presence of pelvic girdles in antiarchs. As antiarchs are placed at the base of the gnathostome radiation in several recent studies, our finding shows that all jawed vertebrates (including antiarch placoderms) primitively possess both pectoral and pelvic fins and that the pelvic fins did not arise within gnathostomes at a point subsequent to the origin of jaws.